2018
DOI: 10.1186/s12871-018-0561-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in career development awards in United States’ anesthesiology and surgery departments, 2006–2016

Abstract: BackgroundAlthough the status of women in anesthesiology has advanced by many measures, obtaining career development funding remains challenging. Here, we sought to compare the characteristics of funded career development awards from the National Institutes of Health (NIH) between the specialties of anesthesiology and surgery. We hypothesized that the two groups differ in percentage of faculty with awards, gender distribution among principal investigators, as well as the number of awards promoting diversity.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The proportion of female EM investigators funded under a K mechanism is higher than reported in other specialties such as surgery and anesthesiology, yet the total number of grants overall awarded to women has not changed. 15 This may demonstrate success of recent initiatives to promote research among female junior faculty. While the higher proportion of female-mentored PIs compared to independent PIs may reflect a trend toward gender equity, an alternative explanation may be that female investigators are not successfully transitioning to independent funding status.…”
Section: Discussionmentioning
confidence: 91%
“…The proportion of female EM investigators funded under a K mechanism is higher than reported in other specialties such as surgery and anesthesiology, yet the total number of grants overall awarded to women has not changed. 15 This may demonstrate success of recent initiatives to promote research among female junior faculty. While the higher proportion of female-mentored PIs compared to independent PIs may reflect a trend toward gender equity, an alternative explanation may be that female investigators are not successfully transitioning to independent funding status.…”
Section: Discussionmentioning
confidence: 91%
“…Women anesthesiologists have fewer publications as first or senior author in peer-reviewed anesthesiology journals and receive fewer career advancement awards. 13 , 14 , 15 , 16 , 17 , 18 Women anesthesiologists are less likely to receive invitations to speak at external departmental grand rounds. 19 At national anesthesiology meetings, all-men panels predominate, whereas women represent lower percentages of single or keynote speakers.…”
Section: Status Of Women Anesthesiologists Prepandemicmentioning
confidence: 99%
“…33 Scholarly productivity (11 articles) Scholarly productivity is recognised as an important factor for career advancement in academic anaesthesiology. 34 Scholarly productivity, a surrogate for 'success in research', 46 was reported in the literature as grant funding, 34,35 recognition awards, 6,36 authorship, 8,29,35,37e39 and presentations at national or international specialty meetings. 40…”
Section: Compensation (Two Articles)mentioning
confidence: 99%
“…Mayes and colleagues 34 reviewed the career advancement awards granted by the US National Institutes of Health (K01, K08, and K23 awards) between 2006 and 2016. They found that women were the recipients of 29 (33%) of the total 88 career development grants awarded to anaesthesiologists during that period.…”
Section: Grant Funding (Two Articles)mentioning
confidence: 99%